Título Padrão - LIMA-NETO, Vicente de; CARVALHO, Ana Paula Lima de (Revista de Letras, 2022)
e understand that texts, as participants of genres, do not work in a vacuum. In the real world, as phenomena that organize life and society, genres are related in different ways. In Brazil (MARCUSCHI, 2000; BONINI, 2011; BEZERRA, 2012; 2017; ARAÚJO, 2006; 2021) and abroad (BHATIA, 2004; SWALES, 2004; BAZERMAN, 2005) there are authors that have already focused on the conceptualization of different genre grouping, from different theoretical affiliations. Following this perspective, this work aims to characterize and discuss one more type of generic grouping, which we call a composite of genres. Based on rhetorical genre studies (MILLER, 2009; 2015; BAZERMAN, 2005; 2009) and Textual Linguistics (CAVALCANTE et al; 2019), we analyzed an example of three types of composites in different media – print, audiovisual and digital –, in which we verify how different genres relate each other and are realized themselves by texts. The results, still incipient, point to two characteristics that differentiate what we have called composite from other genre grouping: the updating of different genres in the same enunciative space and the interrelationship between them, established by a discursive–pragmatic link or technical link, which will vary depending on the media used, without any of the genres losing its peculiarities. Keywords: Genre grouping. Composite of genres. Genre analisys.